Advances in accounting education teaching and curriculum innovations. Vol. 17 - Rupert, Timothy J.; Kern, Beth Burchfield, 1958- (Emerald, 2015)
Advances in accounting education : teaching and curriculum innovations publishes both nonempirical and empirical articles dealing with accounting pedagogy. All articles explain how teaching methods or curricula/programs can be improved. Nonempirical papers are academically rigorous, and specifically discuss the institutional context of a course or program, as well as any relevant tradeoffs or policy issues. Empirical reports exhibit sound research design and execution, and develop a thorough motivation and literature review, including references from outside the accounting field, where appropriate.
Keywords: Business & Economics -- Accounting -- General.; Accounting.; Finance & accounting.; Accounting -- Study and teaching.; Finance -- Study and teaching.; elektronické knihy; electronic books